The Influence of Tax Fairness and Tax Understanding on Tax Evasion (Perceptions of Students in the Accounting Program, Faculty of Economics, Advent Indonesia University) - Permata, Elizabeth Vania; Simbolon, Remista (Eduvest - Journal of Universal Studies, 2023)
The study is meant to evaluate the impact of justice and understanding of taxes on tax evasion according to the perceptions of students at the Indonesian Adventist University Accounting Study Program, Faculty of Economics. There were 55 respondents involved, obtained through a purposive sampling method. SPSS version 22 software was used to analyze multiple regressions. The research yielded the following conclusions: (1) tax justice has no bearing on tax evasion; (2) tax understanding has no bearing on tax evasion; and (3) tax justice and tax understanding have no bearing on tax evasion.